1990
DOI: 10.1002/jcp.1041420110
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipocortin I in the glucocorticoid induction of the terminal differentiation of a human squamous carcinoma

Abstract: The human squamous cell carcinoma SqCC/Y1 undergoes spontaneous terminal differentiation in the confluent state. The degree of maturation was markedly increased by glucocorticoids and by both human recombinant and placental lipocortin I. Western analyses demonstrated cellular secretion of lipocortin into the medium. Glucocorticoid-induced maturation was antagonized by a lipocortin I-specific monoclonal antibody, by phospholipase A2 (PLA2), and by arachidonic acid. Induction of the differentiation of SqCC/Y1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…In the tumorous and for serine/threonine kinases such as protein kinase C. 24 part of HCC, AX-I was stained in the cytoplasm of the AX-I also is thought to be involved in the cellular signal trans-cancer cells. The localization of AX-I mRNA in the nontuduction associated with inflammation, 13,14,25 differentia-morous and tumorous regions of HCC shown by in situ tion, 29,30 and proliferation. [31][32][33] We have already shown that hybridization was similar to that of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tumorous and for serine/threonine kinases such as protein kinase C. 24 part of HCC, AX-I was stained in the cytoplasm of the AX-I also is thought to be involved in the cellular signal trans-cancer cells. The localization of AX-I mRNA in the nontuduction associated with inflammation, 13,14,25 differentia-morous and tumorous regions of HCC shown by in situ tion, 29,30 and proliferation. [31][32][33] We have already shown that hybridization was similar to that of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we al. 29 have reported that the protein may act by promoting showed that some AX-I -positive hepatocytes in the tumorin the differentiation of squamous cell carcinoma. We anaous and nontumorous tissues of HCC were found to have lyzed the relationship between AX-I expression and the derived from a specific subset of parenchymal cells (stem histological grades of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Violette et al (1990) demonstrated that hydrocortisone caused the terminal differentiation of a human squamous cell carcinoma line and that this effect was neutralised by the co-presence of a monoclonal anti-lipocortin antibody but not by a nonneutralising anti-lipocortin 1 monoclonal (i.e. an antibody which binds the protein but does not prevent its biological effect).…”
Section: Discussionmentioning
confidence: 99%
“…Annexins are a structurally related family of Ca 2+ binding proteins of undetermined biological function; various annexins have been implicated in cellular processes, including modulation of phospholipase A2 activity (Crompton et al, 1988), membrane skeletal linkage (Roy-Choudhury et al, 1988), proliferation (Schlaepfer andHaigler, 1990), differentiation (Violette et al, 1990), inflammation (Vishwanath et al, 1992), and blood coagulation (Tait et al, 1988). Annexin I (lipocortin 1, ANX-I, p35) is a substrate for the EGFstimulated tyrosine kinase and is postulated to be involved in mitogenic signal transduction.…”
Section: Introductionmentioning
confidence: 99%